I-PASS Handoff Curriculum: Faculty Development Resources - Jennifer O'Toole; Theodore Sectish; Amy J. Starmer; Glenn Rosenbluth; Daniel West; Christopher Landrigan; April D. Allen; Elizabeth Noble; Rajendu Srivastava; Lisa L. Tse; Jennifer Hepps; Joseph Lopreiato; et al. (Association of American Medical Colleges, 2013)
Abstract Communication failure is the leading root cause of sentinel events in hospitals. The increase in the number of handoffs related to new duty-hour standards in teaching hospitals creates additional opportunities for communication failure. The lack of standardized handoff processes in North American teaching hospitals prompted the I-PASS Study Group to create this curriculum as the educational intervention in a multi-site research study aimed at reducing medical errors and standardizing the handoff process in 10 pediatric residency programs across North America. The I-PASS Handoff Curriculum: Faculty Development Resources is one of six resources which are part of the I-PASS Handoff Curriculum Collection, created by a group of pediatric educators, health services researchers, and hospitalists to teach a standardized approach to handoffs in inpatient settings. This collection is a comprehensive, evidence-based, and consensus-driven suite of educational materials created for a multisite study that includes the following complementary components: the Core Resident Workshop, Handoff Simulation Exercises, Computer Module, the Campaign Toolkit, and Faculty Observation Tools. The Faculty Development Resources collection contains all of the necessary materials that an institution, division, or training program will need to educate and train faculty and Chief Resident champions for implementation of the I-PASS Handoff Program at their site. Also included in Faculty Development Resources is an interactive Faculty Development Presentation which features a series of simulation videos that allow faculty the opportunity to practice observing and evaluating handoffs. Speaker notes are provided to assist presenters. In addition, within the Faculty Development Resources, there are comprehensive instructions on how to use the Faculty Observation Tools to provide effective learner feedback.